Government Response in Managing Citizen Journalism in Pandemic Times - Thetanaya, Thetanaya; Nurcholis, Chanif (KnE Social Sciences, 2022)
The Covid-19 pandemic has been going on for the past two years. During this time, there has been a lot of news about Covid-19, which has affected the attitudes of citizens including through social media. There has been a rise in journalism among citizens who write about the pros and cons of the government efforts to manage the recovery from the pandemic. There are still debates about whether citizen journalism can be used as a form of public participation. Public participation in the context of open government can demonstrate citizen involvement in the policy-making process of democratic countries. The response of governments to citizen journalists varies. Some countries have banned them, some have ignored them, and some have documented their opinions. What about Indonesia? To what extent do the central and local governments accommodate and respond to their citizens who write about their complaints and experiences? This paper employed qualitative descriptive methods using secondary data and analyzed the culture and behavior of citizens and governments within the democratic context. There have been changes in opinions and a polarization in aims to spread accurate news. As a result, the correct information about Covid-19 could be obtained not only from official government information, but also from the citizen journalists who were given space by the central and regional governments in Indonesia. Local governments have used citizen journalism to evaluate several policies during the pandemic times. The central government accommodates citizen journalism, but the government policies are issued using a top-down approach. Trying to prevent citizen journalism can lead to backlash from citizens. This article aimed to provide an analysis from the public administration perspective about the importance of the involvement of citizen participation during the pandemic times, especially when the media and experts are forced to be silent. Keywords: pandemic, public participation, citizen journalism, government openness, policy making, culture and community behavior